Serum visfatin in chronic renal failure patients on maintenance hemodialysis: A correlation study - Abdel Wahab M Lotfy; Nagwa A Mohammed; Hanan M El-Tokhy; Fatma A Attia (SpringerOpen, 2013)
Background and aim of work Endothelial dysfunction, atherosclerosis, and cardiovascular disease are strongly linked to chronic kidney disease. It has been hypothesized that visfatin may play an important role in uremia-related atherosclerosis and the relation between visfatin and endothelial dysfunction has been proved. We aimed to study and characterize the relation of visfatin to some clinical and biochemical parameters among chronic renal failure (CRF) patients on regular hemodialysis. Patients and methods This study was carried out on a total of 90 individuals, divided into two groups: group A included 68 patients with CRF on regular hemodialysis (44 men and 24 women) and group B included 22 healthy individuals as controls (four men and 18 women). All participants were subjected to the following: full clinical assessment, BMI assessment, FBS (Fasting blood sugar), PPBS (postprandial blood sugar), Hb level, lipid profile, serum urea, creatinine, potassium, phosphorus, and serum visfatin. Results Serum visfatin concentration was significantly high in group A (uremic on hemodialysis) compared with group B (control) (48.95 ng/ml ±11.62 compared with 22.65 ng/ml ± 5.24; P < 0.001); a highly significant positive correlation was found between serum visfatin and serum low-density lipoprotein (r = 0.39; P < 0.001) and a significant positive correlation between serum visfatin and serum triglycerides and serum uric acid (r = 0.28; P < 0.05 and r = −0.24; P < 0.05), respectively, whereas a highly significant negative correlation between serum visfatin and Hb (r = −0.43; P < 0.001) and a significant negative correlation between serum visfatin and serum urea (r = −0.25; P < 0.05), blood sugar, both fasting and postprandial (r = −0.34; P < 0.001 and r = −0.39; P < 0.001), respectively, were found in the patients in group A, without a significant correlation either to high-density lipoprotein, serum creatinine, the etiology of CRF, or to the duration of dialysis in the patients in group A. Conclusion This study proves the association of serum visfatin with CRF, unrelated to the biochemical parameter of kidney functions; however, further studies to examine visfatin expression within renal tissue may clarify its definitive role in CRF.